Pengaruh Modal Intelektual Dan Pengungkapan ModalIntelektual Pada Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Kontrol (Studi pada Perusahaan yang Melakukan Initial Public Offering (IPO) di Bursa Efek Indonesia ) - Wulandari, Tyas, Banu Witono, SE., M.Si., Ak, Shinta Permata Sari, SE (2014)
The purpose of this research is to examine the influence of intellectual capital and intellectual capital disclosure to the value of the firm with size firm as control variable. The research data are taken from the prospectus issued by company which doing an Initial Public Offering (IPO) during 2006 to 2013, selected by purposive sampling method. The hypothesis tested by using multiple regression analyzed. The result shows:1) intellectual capital does not have an influence to firm's value, 2) Intellectual capital disclosure has an influence to the value of the firm, 3) Size firm as control variable has an influence to the value of the firm.